Correlation of p53 oligomeric status and its subcellular localization in the presence of the AML-associated NPM mutant - Aleš Holoubek; Dita Strachotová; Kateřina Wolfová; Petra Otevřelova; Sára Belejová; Pavla Röselová; Aleš Benda; Barbora Brodská; Petr Herman (PLoS ONE, 2025)
Tumor suppressor p53 is a key player in the cell response to DNA damage that suffers by frequent inactivating aberrations. Some of them disturb p53 oligomerization and influence cell decision between proliferation, growth arrest and apoptosis. Active p53 resides mostly in the nucleus, degradation occurs in the cytoplasm. Acute myeloid leukemia (AML)-related mutation of NPM (NPMmut) induces massive mislocalization of p53 to the cytoplasm, which might be related to leukemia initiation. Since both proteins interact and execute their function as oligomers, we investigated the role of perturbed p53 oligomerization in the p53 mislocalization process in live cells by FLIM (fluorescence lifetime imaging microscopy), fluorescence anisotropy imaging (FAIM), fluorescence cross-correlation spectroscopy (FCCS) and immunochemical methods. On a set of fluorescently labeled p53 variants, monomeric R337G and L344P, dimeric L344A, and multimeric D352G and A353S, we correlated their cellular localization, oligomerization and interaction with NPMmut. Interplay between nuclear export signal (NES) and nuclear localization signal (NLS) of p53 was investigated as well. While NLS was found critical for the nuclear p53 localization, NES plays less significant role. We observed cytoplasmic translocation only for multimeric A353S variant with sufficient stability and strong interaction with NPMmut. Less stable multimer D352G and L344A dimer were not translocated, monomeric p53 variants always resided in the nucleus independently of the presence of NPMmut and NES intactness. Oligomeric state of NPMmut is not required for p53 translocation, which happens also in the presence of the nonoligomerizing NPMmut variant. The prominent structural and functional role of the R337 residue is shown.